The effects of 10-week plyometric training program on athletic performance in youth female handball players - Gaamouri, N.; Hammami, M.; Cherni, Y.; Rosemann, T.; Knechtle, B.; Challey, M. S.; van den Tillaar, R. (Frontiers in Sports and Active Living, 2023)
Purpose: The aim of the study was to investigate the effects of a 10-week plyometric training (PT) on changes of direction, jumping ability, repeated sprint ability, and both muscular strength and power in youth female handball players.